Clinical Profile of Indoor Covid-19 Patients at a Medical Institute In India: A Retrospective analysis - Khwaja, Mariyam; Chopra, Deeapk; Verma, Pankaj Kumar; Jauhari, Nidhi; Shehnaz, Shadiya (Indian Journal of Community Health, 2022)
Background: COVID-19 has caused a very high burden of morbidity and mortality across the world, India being also badly affected. The disease has a wide spectrum ranging from asymptomatic to severe illness and death. Research work on the epidemiological and clinical profile of patients is scarce in India. Objectives: This study was conducted to know the clinico-epidemiological profile of indoor hospitalized Covid 19 patients. Methods: a retrospective analysis (record based) conducted at a designated COVID tertiary care center. Study period-1st August 2020 to 31st October 2020. Study Unit- Laboratory confirmed COVID 19 patients admitted in the hospital. Sample size- All the 894 patients with complete record were included in the study. Results: The mean age was 47.68± 17.62 years. Around 14.1% of the population was asymptomatic. 75.7% were classified as having a mild disease. The cure rate was 82.9% and deaths were reported in 9.4%. Conclusions: Our findings were similar to findings observed in other studies. A positive significant correlation was noticed between age, duration, clinical severity and outcome of patient. The clinical severity was also found to be associated with age, duration of symptoms and outcome of patient